Lithium-ion (Li-ion) battery state of charge estimation - Zhang, Yu. (2013)
The goal of this project is to develop a model to estimate the state-of-charge (SOC) of batteries in real-time. In battery, the state-of-charge serves as indicator of remaining capacity/energy as well as indicator of when battery needs to recharge. In some applications e.g. electric vehicle, an accurate estimate of SOC is necessary since the performance and operation of vehicle is dependent on battery as the only energy source. To validate the model, experimental tests will be conducted. The experimental tests are based on standard battery performance and characteristics, such as constant discharge current at different operating temperature and different discharge current rates at constant operating current.